Counterinsurgency and the People's War in El Salvador - Villalobos, Marty (Kasarinlan: Philippine Journal of Third World Studies; Vol 3 No 1 (1987), 2007)
Low Intensity Conflict (LIC) advocates “total war” in all fronts—economic, social, political, and psychological. El Salvador has served as the main model for the application of LIC. In this study, the author will look into how the anti-imperialist or revolutionary forces in El Salvador responded to LIC and how they were able to frustrate this counter-insurgency scheme of the United States and the Duarte regime. He will also tackle how these forces further developed their revolutionary struggle. The paper will deal mainly with the Salvadoran situation from 1981 up to the present.